Mental health law, policy & program in India - A fragmented narrative of change, contradictions and possibilities - Ketki Ranade; Arjun Kapoor; Tanya Nicole Fernandes (Elsevier, 2022)
There has been a long-standing history of over 150 years of mental health legislation in the Indian sub-continent. India formulated its National Mental Health Program (NMHP) in 1982 and National Mental Health Policy (MHP) only in 2014. In this paper we mark significant influences on the evolution of mental health law, policy and program in India starting from colonial laws. We suggest that discursive continuities from these colonial laws have existed for a few decades in post-independence India. International influences of deinstitutionalization and growth in community psychiatry took root in India by the late 1970s and considerably shaped mental health program thinking. The decade of 2000s with two major international developments, the UN Convention on Rights of Persons with Disabilities (CRPD) as well as Movement for Global Mental Health (MGMH) have had a significant impact on the mental health sector in India. We comment on a disjuncture between the progressive frames of the current mental health law and policy framework on the one hand and the national and district mental health programs in the country on the other. We then focus on technology assisted solutions for mental health care and their promise as widely promoted by the state and the market and what these mean for a country like India. Throughout the paper, we raise critical questions regarding dominance of western bio medical psychiatry as the epistemic frame guiding policy imagination at the cost of diverse, community resources and practices.